The impact of cheap oil on gas markets - Jensen, J; Kelly, M (Oxford Institute for Energy Studies, 1990)
It is often assumed that oil can increase its share of energy markets fairly quickly if its price drops relative to competing fuels. Since oil is already the dominant fuel in the transportation sector, gains at the expense of other fuels must come from elsewhere. The slow pace of fuel conversion decisions in the residential and commercial sectors makes it unlikely that price changes will have any perceptible impact in those sectors in the short-run. Thus it is logical to expect that, if changed oil price signals are to have any short-run impact at all, they are most likely to make themselves felt in the industrial and power generation sectors.